The principle of non-criminalization of victims of trafficking and exploitation in the theory of crime - Rodríguez Salinas, Sergio Enrique (2024)
This article examines how the principle of noncriminalization of victims of human trafficking and exploitation, based on international human rights law, is transferred to criminal theory. It begins by analyzing the role of criminal dogmatics, particularly within academia, in the judicial application of criminal law.From this perspective, the construction of criminal norms is examined in its argumentative and communicative dimensions, emphasizing two key aspects: the norm’s recipient and its content. In this context, the traditional positioning of imputability and the requirement of alternative conduct within culpability is questioned, as well as the distinction between typicity and unlawfulness. Human trafficking and exploitation are characterized as phenomena involving relationships of dominance or control over victims, and the principle of non-criminalization is justified based on the need for their protection, as established in the Palermo Protocol.Finally, it is concluded that this principle entails the application of a case of individual non-exigibility, preventing the State from addressing trafficking victims as recipients of criminal norms, which has direct implications for criminal proceedings and the protection of their rights.